Molecular cloning of region-specific chorion-encoding RNA sequences. - Regier, J C (1984)
We have constructed a cDNA clone library from poly(A)+ RNA of very-late-period choriogenic silkmoth follicles. Clone DNAs that hybridize preferentially to RNA from the aeropyle crown region of the follicle (versus the flat region) were selected, and all could be placed in one of two homology groups. The two groups represent sequences encoding the very-late-period chorion proteins E1 and E2; this was established by hybrid-selected translation coupled with specific antibody precipitation. Regionalized synthesis of chorion proteins is restricted to the very late period, and its control can now be studied at the nucleic acid level.